Development an integrated strategic framework for critical influential issues on building maintenance success in Malaysian Public Universities - Mohammed Hauashdh, Ali Hamid (2022)
In recent years, there have been several concerns regarding building maintenance of Malaysian public buildings, particularly educational buildings, which are continually increasing and experiencing severe issues. However, previous studies have not yet identified the issues related to building maintenance practices and their influences on building maintenance success in Malaysian public universities. Therefore, this research aimed to develop an integrated strategic framework for critical influential issues on building maintenance success in Malaysian public universities (MPUs). The present research has employed a case study as the research strategy and a sequential mixed method design as the research design, which comprises quantitative and qualitative methods. This study started with the collection and analysis of quantitative data (via a questionnaire survey); this first phase was followed by the collection and analysis of qualitative data (via semi-structured in-depth interviews). The quantitative data analysis was performed using SPSS and PLS-SEM, while the analysis of qualitative data was carried out using the content analysis technique. After that, the integration of quantitative and qualitative results was conducted to develop the framework. The research findings identified building maintenance issues, assessed their impacts on building maintenance success, and proposed strategies to address those issues and their influences in MPUs. The identified issues were related to organisational issues, human resource issues, technical issues, financial issues, building user issues and university expansion issues. Organisational issues had a large impact, while human resources had no impact, technical issues had minor impact, and financial, university expansion, and building user issues had medium impact on the overall building maintenance success. As a result, the following six strategies have been proposed for successfully implementing building maintenance in MPUs: organisational strategy; financial strategy; university expansion strategy; technical strategy; human resources strategy; building users strategy. These strategies have the potential to address the identified issues and their consequences. Overall, this research will guide maintenance organisations and other involved stakeholders in MPUs to carry out effective maintenance practices. It will also provide information to those concerned about the building maintenance industry, allowing them to improve their perception of successful maintenance.